CODE-MIXING USAGE IN FATHIA IZZATI’S YOUTUBE CHANNEL VIDEO - Arnila Septia Cahaya; Eva Nurchurifiani; Innayah Hanum; Maria Lovelita Vinantiastuti (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
Sociolinguistics considers code mixing as an important area of study, particularly as a sign of bilingualism, where individuals use more than one language. Code-mixing transpires when individuals integrate different languages in their speech or sentences. The objective of this investigation is to recognize the varieties and motivations behind code-mixing as evidenced in a YouTube video by Fathia Izzati. The study employs a descriptive qualitative approach to showcase the findings derived from the analysis of the data. In order to classify the forms of code-mixing, specifically intra-sentential, intra-lexical, and those involving a shift in pronunciation, the researchers utilize Hoffman's theory. The subject data consists of Fathia Izzati's utterances in a video titled "Realistically set & reach your goals" on her YouTube channel. The researchers discovered that the most frequently used type of code-mixing was inter-sentential code-mixing, accounting for 96% of the instances, and discussing a specific topic was the most common reason, representing 44% of the occurrences in the video. The implications of this study are presented in the form of an article, aiming to contribute new insights into the types and reasons for code-mixing usage.